Avaliatividade: estratégia discursiva na representação de atores sociais - Jornada, Daniela Zenatto (2009)
This work believes that language, when it is put in action, allows as the expression of someone world s experiences, as the building of representations of the same subject and others. Since we understand that discursive practices are able to project identities, we chose to investigate versions of reality expressed in opinion s article from the journalist Diogo Mainardi when he represents, via discourse, president Lula, Workers Party, and Lula s government. We intend, in fact, to answer the following question: how the journalist Diogo Mainardi realizes linguistically the president Lula s representation, as well as the representation of his party and his government? The answer to this central question passes also through the author ethos constitution. Then, we examined, in this study, different linguistic ways which Mainardi uses in order to build as an image of himself, as an image of the biggest figure of brazilian s politics hierarchy. To do this, we based our work on appraisal theory, from Martin & White (2005), on social actor representation s theory proposed by van Leeuwen (1997), and on transitivity system by Halliday & Matthiessen (2004). The ethos constitution was investigated based on Amossy s researches (2005). Our results pointed out negative judgments of Mainardi concerning the actors we discussed. We detected predominance of capacity social esteem judgments, in representations of Lula, and predominance of property social sanction judgments, in people who belongs to his government. So, we conclude that the pejorative way Mainardi represents Lula is just a personal implication and, because of it, should not be considered in terms of evaluation of president s behavior, either in terms of building his identity.